2011
DOI: 10.1007/s10815-011-9539-3
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of whole ovaries with vascular pedicles: vitrification or conventional freezing?

Abstract: Vitrification seems to be more suitable than conventional freezing for cryopreservation of whole ovaries. However, further studies are required to improve the efficacy of vitrifying whole ovaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 42 publications
(54 reference statements)
0
24
0
Order By: Relevance
“…Sugimoto et al (2) found that eight out of nine animals that had received transplanted vitrified ovary reestablished their cyclicity; histology revealed healthy antral follicles 3 months after transplantation. In other experiments on vitrification of whole ovaries in the sheep (41) and cow (42), some success have been reported. However, with human ovarian strips, the efficacy of slow-freezing versus vitrification is controversial (43,44).…”
Section: Discussionmentioning
confidence: 98%
“…Sugimoto et al (2) found that eight out of nine animals that had received transplanted vitrified ovary reestablished their cyclicity; histology revealed healthy antral follicles 3 months after transplantation. In other experiments on vitrification of whole ovaries in the sheep (41) and cow (42), some success have been reported. However, with human ovarian strips, the efficacy of slow-freezing versus vitrification is controversial (43,44).…”
Section: Discussionmentioning
confidence: 98%
“…Some studies compare Fig. 4 a, b The stromal cell density in different groups vitrification versus slow-cooling by comparing parameters such as follicle viability, histological examination and apoptosis assessment, or hormone concentrations in the culture supernatants, but no consensus has yet been reached [23,24]. Having analyzed the preexperimental data combined in previous studies, we chose slow-cooling in our study, since it enables the precise adjustment of the temperature gradients to achieve an accurate cooling rate through the entire ovary and leads to less ice formation.…”
Section: Discussionmentioning
confidence: 99%
“…In sheep studies, most follicular population was lost because of vascular complications after transplantation with vascular anastomosis [16,17,23], although a successful pregnancy and an ovarian function of 6 years were reported after whole ovary cryopreservation and autotransplantation in sheep [12,32]. In cow study, the results were also not encouraging [24,33]. To date, it has not been possible to perform whole ovary transplantation after cryopreservation in humans because of technical difficulties in cryopreservation.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure was carried out according to the protocol that we previously reported [24]. Warming of ovary One month later, the ovaries were removed from the Dewar and held in air at room temperature for 2 min before plunging in a water bath at 37°C for another 2 min with gentle shaking.…”
Section: Ovarian Perfusion and Cryopreservation Of Ovarymentioning
confidence: 99%
See 1 more Smart Citation